The Rich Man and Lazarus: an apocryphal interpolation? - Caïrus, Aecio E. (2006)
The story in Luke 16:19-31 may have been written for "Virtutes Iohanni", a Gnostic gospel written an author acquainted with both the original form of Luke (i.e., the parable of the prodigal son) and the gospel of John (i.e., the resurrection of Lazarus), and interpolated by others into the text of the canonical gospel before 180 C.E. It fits the apocryphal narrative but not the Lukan context, and Ignatius does not seem to know this story. The connection of ideas between the preceding and following verses in Luke also suggests an interpolation, as does its uncharacteristic opening doublet, an unlikely sequence of events in the resulting narrative, and a peculiar eschatology. This cautions against basing doctrine on this particular story.
Keywords: Reicher Mann und armer Lazarus; Gleichnis